Analisis Manajemen Risiko pada UMKM Bengkel Motor - Muhammad Alfin Alfarizi; Mario Maulana Wardhana2; Nisa Febrianti; Muhammad Shoffan Anbiya; Alfiana Alfiana (Indonesia Economic Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs), such as motorcycle repair shops, face various challenges that threaten their business continuity. This study analyzes risk management at the Mang Wahyu Motorcycle Workshop MSME in Bandung City. Using a descriptive qualitative approach through a case study, data was collected via in-depth interviews and observation. The results identify a number of critical risks categorized into four main aspects: (1) Market Risk, including declining demand for conventional motorcycle services and price competition from digital competitors; (2) Operational Risk, in the form of repair delays due to obsolete equipment and dependence on a single supplier; (3) Human Resource (HR) Risk, covering internal conflicts and limitations in technical competence; and (4) Financial Risk, namely price fluctuations for spare parts and cash flow disruptions. Further analysis using a risk matrix shows that most risks have a high impact level and require immediate treatment. As an implication, this study recommends a set of mitigation strategies, such as service diversification towards electric vehicles, improvement of operational processes, enhancing HR capacity through training, and strengthening financial management. The implementation of these recommendations is expected to increase business resilience and support the sustainability of motorcycle workshop MSMEs amidst a competitive market dynamic.